General physics of "mystical face apparitions": Why people come to believe in hypothetical "Virgin Mary or Jesus faces" - Pirot, Florent (European Journal of Applied Sciences, 2021)
The various natural disasters involving forms of sedimentation explain concretion of face remains on tufs that can later happen to be found by humans or even be accidentally taken by industrial works and reappar randomly. One case is given. Frequent apparition of such remains have obviously spread, in other groups of people the feeling of divine signs, “apparition of the Virgin Mary” for instance in recent times. Already existing articles of the author demonstrate how natural disasters happen against tribes and groups that have not followed natural rules but have become exploitative, explaining why archaeological work is not extremely interesting.